2002
DOI: 10.1530/eje.0.1460067
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency and replacement in hypopituitary patients previously treated for acromegaly or Cushing's disease

Abstract: Objective: To compare baseline characteristics in adult patients with growth hormone (GH) deficiency (GHD) who had previously been treated for Cushing's disease or acromegaly with data from patients with GHD of other aetiologies. To study the effects of GH therapy in those patients who had completed at least 6 months of GH replacement. Design: Data from a large outcomes research database (KIMS (Pharmacia International Metabolic Database)). Methods: 135 patients were identified with previous Cushing's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 32 publications
(14 reference statements)
13
82
1
Order By: Relevance
“…Furthermore, we confirmed that there are no significant differences in terms of metabolic parameters between cured acromegalic patients and matched adults with other pituitary diseases with severe GHD, in agreement with previous observation (22). On the contrary, a recent study has reported a more impaired cardiovascular risk profile in ten GHD patients with previous acromegaly as compared with other GHD patients (23).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we confirmed that there are no significant differences in terms of metabolic parameters between cured acromegalic patients and matched adults with other pituitary diseases with severe GHD, in agreement with previous observation (22). On the contrary, a recent study has reported a more impaired cardiovascular risk profile in ten GHD patients with previous acromegaly as compared with other GHD patients (23).…”
Section: Discussionsupporting
confidence: 92%
“…However, it should be noted that in this study the radiotherapy patients had a longer period of GHD prior to replacement (11.5 vs 4.7 years) and that those treated with radiotherapy have a tendency towards most severe disease. GHD secondary to Cushing's disease and acromegaly is not associated with baseline differences in body composition when compared with other causes of GHD (34).…”
Section: Clinical Characteristics Of the Hypopituitary Gh Deficient mentioning
confidence: 81%
“…Patients with Cushing's disease are known to have a high prevalence of cardiovascular risk factors, even after successful long-term cure of Cushing's disease (20). On the other hand, FeldtRasmussen et al found no differences in WH ratio, BMI, TG, and total, LDL and HDL cholesterol levels between patients with GHD due to previous treatment for Cushing's disease compared with patients with GHD due to other aetiologies (21). In our limited number of patients, we were unable to demonstrate differences in the prevalence of the MS between patients treated for Cushing's disease or acromegaly and patients treated for non-functioning pituitary adenomas, or between patients with producing pituitary adenomas compared with patients with non-functioning adenomas.…”
Section: Discussionmentioning
confidence: 99%